Congenital aortic stenosis: treatment outcomes in a nationwide survey. (3rd September 2017) - Kallio, Merja; Rahkonen, Otto; Mattila, Ilkka; Pihkala, Jaana
Abstract: Objective. To evaluate treatment outcomes of pediatric valvar aortic stenosis (AS) in a nationwide follow-up. Design. Balloon aortic valvuloplasty (BAV) has been the preferred treatment for congenital AS in Finland since the year 2000. All children treated due to isolated AS during 2000–2014 were included in this retrospective study. Treatment outcomes were categorized into Optimal : residual gradient  ≤35 mmHg and trivial or no aortic regurgitation (AR), Adequate: gradient ≤35 mmHg with mild AR, or Inadequate : gradient >35 mmHg and/or moderate to severe AR. Results. Sixty-one patients underwent either BAV ( n  = 54) or surgical valvuloplasty ( n  = 7) for valvar AS at a median age of 29 days (range 6 hours to 16.9 years). The proportion of patients not requiring reintervention at 1, 5, and 10 years was 61%, 50%, and 29% in neonates and 83%, 73%, and 44% in older patients, respectively ( p  = .02); without difference between treatment groups. Larger proportion of patients remained free from valve surgery after optimal BAV result than after adequate or inadequate result ( p  = .01). The reason for the first reintervention was AS in 50%, AR in 36%, and combined aortic valve disease in 16% of cases. Early mortality (before hospital discharge) was 4.9%, and associated with critical AS in neonates. There was no late mortality during the follow-up. Conclusions. Although majority of congenital AS patients require more than one intervention during childhood, an optimal BAV result improves long-term outcome by increasing the proportion of patients remaining free from valve surgery. High long-term freedom from reintervention is attainable also in the neonatal population.